A novel oncostatin M/interleukin‐31 receptor mutation in familial primary localized cutaneous amyloidosis. (1st March 2020) - Adams, R.; Colmont, C.; Mukhtar, A.; Morgan, H.; Patel, G. K.
Abstract: Click here for the corresponding questions to this CME article.